Finite Fracture Mechanics and Cohesive Crack Model_Size effects through a unified formulation - F. Ferrian; P. Cornetti; L. Marsavina; A. Sapora (Fracture and Structural Integrity)
Finite Fracture Mechanics and Cohesive Crack Model can effectively predict the strength of plain, cracked or notched structural components, overcoming the classical drawbacks of Linear Elastic Fracture Mechanics. Aim of the present work is to investigate size effects by expressing each model as a unified system of two equations, describing a stress requirement and the energy balance, respectively. Brittle crack onset in two different structural configurations is considered: (i) a circular hole in a tensile slab; (ii) an un-notched beam under pure bending. The study is performed through a semi-analytical parametric approach. Finally, theoretical strength predictions are validated with experimental results available in the literature for both geometries, and with estimations by the point criterion in the framework of Theory of Critical Distances.